"Theorizing teacher mobility": a critical review of literature. Issue 7 (3rd October 2017) - Vagi, Robert; Pivovarova, Margarita
Abstract: In this critical review of literature, we summarize the major theoretical frameworks that have been used to study teacher mobility. In total we identified 40 teacher mobility studies that met our inclusion criteria. We conclude that relatively few theoretical frameworks have been used to study teacher mobility and those that have been used are lacking in several key areas. Specifically, none of the current teacher mobility theories are able to adequately account for the many teacher- and school-level factors that likely influence teachers' professional decisions. Finally, we suggest a theoretical framework from the organizational psychology literature that can address the shortcomings of theories identified in this review.